Nursing Student Self-efficacy in Psychomotor Skills: Findings From a Validation, Longitudinal, and Correlational Study. Issue 6 (November 2016) - Bulfone, Giampiera; Fida, Roberta; Ghezzi, Valerio; Macale, Loreana; Sili, Alessandro; Alvaro, Rosaria; Palese, Alvisa
Abstract : Student perceptions of self-efficacy (SE) prevent stress and burnout and improve engagement in nursing education, thus increasing learning outcomes. The study aims were to (1) validate a scale measuring nursing SE in psychomotor skills (NSE-PS), (2) describe changes in NSE-PS over time, and (3) explore NSE-PS correlations with burnout and engagement. A total of 1117 nursing students participated. A significant increase in the NSE-PS scores over the years has emerged; in addition, all NSE-PS dimensions were correlated negatively with burnout and positively with engagement.